2017
DOI: 10.1097/md.0000000000007625
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing incidence and mortality among hospitalized patients suffering a ventilator-associated pneumonia

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 42 publications
3
12
2
Order By: Relevance
“…In agreement with other studies [47][48][49][50], the current study showed a male sex predominance. The age of the study patients was higher in the non-survivors group.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with other studies [47][48][49][50], the current study showed a male sex predominance. The age of the study patients was higher in the non-survivors group.…”
Section: Discussionsupporting
confidence: 93%
“…Juthani et al 16 found that male gender was a significant risk factor for CAP (HR 2.07; 95% CI 1.51‐2.83); however, other authors indicated that male gender is a nonsignificant factor for CAP 17 . Previous works have shown that despite the lower incidence of VAP, females with VAP have increased mortality 18 . Sharpe et al 19 found that despite a higher incidence of VAP amongst males (3.8% vs 2.6%, P = .001), mortality was higher in females (24% vs 15%, P = .009).…”
Section: Introductionmentioning
confidence: 99%
“…17 Previous works have shown that despite the lower incidence of VAP, females with VAP have increased mortality. 18 Sharpe et al 19 found that despite a higher incidence of VAP amongst males (3.8% vs 2.6%, P = .001), mortality was higher in females (24% vs 15%, P = .009).…”
mentioning
confidence: 98%
“…Over the last two decades, research has focused mainly on ventilator-associated pneumonia (VAP), and as a consequence, the incidence of this complication has decreased and patient outcomes have improved [25]. In Spain, a recent investigation showed that the incidence rates of VAP improved significantly from 41.7 cases/100,000 inhabitants in 2010 to 40.55 cases/100,000 inhabitants in 2014 [6]. However, VAP is not the only form of HAP; a recent report with data from the US National Inpatient Sample dataset found that nonventilator HAP was associated with mortality, a greater length of hospital stay and an increase in the cost of care [7].…”
Section: Introductionmentioning
confidence: 99%